Literature Review: Myocardial infarction in Young Adult - Ratu Trya Maharani; Nurhikmawati Nurhikmawati; Akina Maulidhany Tahir; Fadillah Maricar; Purwati Pole Rio (ScieClouds Publishing, 2026)
Myocardial infarction (MI) has traditionally been considered a disease of older adults; however, recent evidence indicates an increasing incidence among younger populations. This trend has raised significant clinical and public health concerns because MI occurring during productive years is associated with substantial long-term health, social, and economic consequences. Understanding the risk factors, clinical characteristics, and outcomes of MI in young adults is essential for improving prevention and management strategies. This study aimed to systematically review the current literature regarding myocardial infarction in young adults, with a particular focus on risk factors, clinical characteristics, and patient outcomes. A literature review was conducted using articles retrieved from PubMed, ScienceDirect, and Google Scholar. The search covered publications from 2021 to 2026 using keywords related to myocardial infarction, young adults, acute coronary syndrome, and cardiovascular risk factors. Articles were screened according to predefined inclusion and exclusion criteria. Following the selection process, 20 eligible studies consisting of observational studies, cohort studies, registry analyses, case series, and review articles were included in the final analysis. he findings demonstrate that myocardial infarction in young adults is a growing global health issue. Traditional risk factors, particularly smoking, dyslipidemia, obesity, hypertension, diabetes mellitus, and family history of cardiovascular disease, remain the primary determinants of disease occurrence. Emerging risk factors, including psychosocial stress, sleep disorders, autoimmune diseases, chronic inflammation, and substance abuse, also contribute significantly. Clinically, young patients commonly present with typical chest pain and predominantly single-vessel coronary artery disease, although non-atherosclerotic mechanisms such as spontaneous coronary artery dissection and myocardial infarction with non-obstructive coronary arteries are increasingly recognized. While short-term outcomes are generally more favorable than in older patients, long-term risks of recurrent cardiovascular events and persistent morbidity remain substantial. Myocardial infarction in young adults is a multifactorial condition requiring comprehensive risk assessment, early prevention, and long-term management strategies to reduce future cardiovascular burden.